2013
DOI: 10.3390/ijerph10020446
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an Electronic Cigarette on Smoking Reduction and Cessation in Schizophrenic Smokers: A Prospective 12-Month Pilot Study

Abstract: Background: Cigarette smoking is a tough addiction to break. This dependence is the most common dual diagnosis for individuals with schizophrenia. Currently three effective drugs are approved for smoking cessation: nicotine replacement therapy (NRT), varenicline and bupropion. However, some serious side effects of varenicline have been reported, including depression, suicidal thoughts, and suicide. The use of bupropion also has side effects. It should not be used by people who have epilepsy or any condition th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
164
2
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(180 citation statements)
references
References 44 publications
8
164
2
4
Order By: Relevance
“…In a small pilot study, they appeared to decrease cigarette consumption, [41] and they may be especially useful in reducing consumption in chronic psychiatric (schizophrenic) patients. [42] Sideeffects include mouth and throat irritation, dry cough, nausea and headache, although these appear to decrease over time. Concerns have been raised about the long-term safety of e-cigarettes, particularly with regard to the flavouring used.…”
Section: Electronic Cigarettesmentioning
confidence: 99%
“…In a small pilot study, they appeared to decrease cigarette consumption, [41] and they may be especially useful in reducing consumption in chronic psychiatric (schizophrenic) patients. [42] Sideeffects include mouth and throat irritation, dry cough, nausea and headache, although these appear to decrease over time. Concerns have been raised about the long-term safety of e-cigarettes, particularly with regard to the flavouring used.…”
Section: Electronic Cigarettesmentioning
confidence: 99%
“…[11][12][13][14] However, although there is evidence that e-cigarettes may help some people reduce or even quit smoking, available prospective studies suggest that e-cigarettes are similar to NRT in that most users do not quit smoking. [15][16][17][18][19][20][21] Despite these concerns, a recent cross-sectional, retrospective study found that e-cigarette users in the general population were more likely than NRT users to have quit cigarette smoking. 22 In comparison to cigarettes, available evidence suggests that e-cigarettes are a safer nicotine delivery system.…”
mentioning
confidence: 99%
“…Of these studies, in the study by Polosa et al (52), only 5 of 40 people could quit smoking in the second year (12.5%). This rate was 14.3% (2 of 14 patients) in the study conducted by Caponnetto et al (53). In another randomized controlled study of Caponetto et al (54), no difference was observed with regard to the rates of smoking cessation between people using and not using e-cigarettes.…”
Section: Its Effects On Smoking Cessationmentioning
confidence: 68%
“…In 3 of the 4 existing studies investigating the effect of e-cigarettes on smoking cessation, there was no control group (52)(53)(54). In the fourth study, the efficiency of e-cigarette was compared with 21 mg nicotine patch treatment (55).…”
Section: Its Effects On Smoking Cessationmentioning
confidence: 99%